A prospective study on quality in endoscopic retrograde cholangiopancreatography (ERCP): trend in Italy from the REQUEST study - Donato, Giulio; Occhipinti, Pietro; Correale, Loredana; Spadaccini, Marco; Repici, Alessandro; Anderloni, Andrea; Fugazza, Alessandro; Mosca, Piergiorgio; Tringali, Andrea; Costamagna, Guido; Bulajic, Milutin; de Pretis, Giovanni; Gabbrielli, Armando; Di Matteo, Francesco Maria; Faggiani, Roberto; Ayoubi, Mohammad; De Luca, Luca; Cantù, Paolo; Blois, Matteo; Dell’Amico, Iginio; Maurano, Attilio; Savarese, Maria Flavia; Manes, Giampiero; Ferraro, Raffaella; Barberis, Mauro; Hassan, Cesare; The REQUEST Group (Endoscopy International Open, 2021)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) is a complex procedure with a relatively high rate of adverse events. Data on training of operators and fulfillment of quality indicators in Italy are scarce. The goal of this study was to assess the overall quality of ERCP in Italy compared to international standards.Patients and methods This was a prospective, observational study from different Italian centers performing ERCP. Operators answered a questionnaire, then recorded data on ERCPs over a 1-to 3-month period.Results Nineteen Italian centers participated in the study. The most common concern of operators about training was the lack of structured programs. Seven/19 centers routinely used conscious sedation for ERCP. Forty-one experienced operators and 21 trainees performed 766 ERCPs: a successful deep biliary cannulation in native-papilla patients was achieved in 95.1 % of cases; the post-ERCP pancreatitis (PEP) rate was 5.4 % in native-papilla patients; cholangitis rate was 1.0 %; bleeding and perforation occurred in 2.7 % and 0.4 % of the patients, respectively.Conclusions This study revealed that, overall, ERCP is performed in the participating Italian centers meeting good quality standards, but structured training and sedation practice are still subpar. The bleeding and perforation rate slightly exceeded the American Society of Gastrointestinal Endoscopy indicator targets but they are comparable to the reported rates from other international surveys.